নারী প্রতিনিধিত্ব ও রাজনীতি - গুহঠাকুরতা, মেঘনা; বেগম, সুরাইয়া; আহমেদ, হাসিনা (ঢাকা : সমাজ নিরীখাণ কেন্দ্র, 1997)
On the representation and role of women in society and politics, study with respect to Bangladesh; contributed articles.
In Bengali.
Keywords: Women -- Bangladesh -- Social conditions; Women -- Political activity -- Bangladesh